Distributed Applications and Interoperable Systems : 13th IFIP WG 6.1 International Conference, DAIS 2013, Held as Part of the 8th International Federated Conference on Distributed Computing Techniques, DisCoTec 2013, Florence, Italy, June 3-5, 2013. Proceedings - Taïani, Francois; Dowling, Jim (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 13th IFIP WG 6.1 International Conference on Distributed Applications and Interoperable Systems, DAIS 2013, held in Florence, Italy, in June 2013, as part of the 8th International Federated Conference on Distributed Computing Techniques, DisCoTec 2013. The 12 revised full papers and 9 short papers presented were carefully reviewed and selected from 42 submissions. The papers present state-of-the-art research results and case studies in the area of distributed applications and interoperable systems focussing on cloud computing, replicated storage, and peer-to-peer computing.